2011
DOI: 10.1007/s10334-011-0270-y
|View full text |Cite
|
Sign up to set email alerts
|

MR safety: simultaneous B 0, dΦ/dt, and dB/dt measurements on MR-workers up to 7 T

Abstract: The findings in this work indicate that both translations and rotations in the vicinity of an MR system should be taken into account, and that a single regulatory action level might not be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…, Table ) measured temperature shifts of −4.5°C on average at 9.4T which is in very good agreement with our results at the isocenter of the small animal imaging system of −4.4°C on average (Table ). In Groebner et al a decrease of 2.6°C was observed at a 7T whole‐body system which is in excellent agreement with our measurements at 7T in the fringe field (9.4T system) and at isocenter (7T system) of −2.6°C and −2.7°C (Table ). Thus, these temperature differences are solely related to the magnetic field strength, and do not depend on the MR system type.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…, Table ) measured temperature shifts of −4.5°C on average at 9.4T which is in very good agreement with our results at the isocenter of the small animal imaging system of −4.4°C on average (Table ). In Groebner et al a decrease of 2.6°C was observed at a 7T whole‐body system which is in excellent agreement with our measurements at 7T in the fringe field (9.4T system) and at isocenter (7T system) of −2.6°C and −2.7°C (Table ). Thus, these temperature differences are solely related to the magnetic field strength, and do not depend on the MR system type.…”
Section: Discussionsupporting
confidence: 92%
“…In this work, we showed that the precision of the measurement is critically dependent on the type of fiber‐optical sensor that is applied for temperature measurements in the magnetic field. If sensors with a semiconductor measurement method are used, and sensor calibration is performed outside the magnetic field, field‐strength dependent deviations will occur, as was partly also described in earlier works .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…There is evidence that physiological effects, such as vertigo, metallic taste, and dizziness are related to the spatial fall-off ( dB 0 / dz ) of the fringe field and to the diamagnetic force B 0 * dB 0 / dz (Kangarlu et al, 1999; Liu et al, 2003; Cavin et al, 2007; Glover et al, 2007; Glover and Bowtell, 2008; Groebner et al, 2011; Budinger et al, 2016). …”
Section: Other Noteworthy Challenges Related To Uhf Technologymentioning
confidence: 99%
“…Moreover, since the growing interest of the MR scientific community in developing devices for measurement of static magnetic fields and personal MR dosimeters [22,23], this tool can be used to validate and calibrate this kind of instrument.…”
Section: Resultsmentioning
confidence: 99%